Nanocrystallization of Griseofulvin Prior to Its Tablet Formulation Improves the Drug Delivery - Olorunsola, Emmanuel O; Ekuma, Jennifer U.; Femi-Oyewo, Mbang N.; Orakwe, Clifford A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background: Griseofulvin belongs to Class II in the Biopharmaceutics Classification System. This study aimed at enhancing the delivery of this antifungal agent by nanocrystallizing the drug powder before the tablet formulation. Methods: Two forms of griseofulvin nanocrystals (GRF3 and GRF2) were prepared with and without the inclusion of polysorbate 80 respectively. The two forms of the nanocrystals and the unprocessed drug (GRF1) were separately used to formulate griseofulvin tablets. Each form of the drug was formulated using two different binder concentrations (3% and 6% w/w acacia gum) employing the wet granulation method. Physical and release properties of the tablets were determined using the compendial and the non-compendial methods. Results: The mean weight of the formulated tablets ranged from 0.31 – 0.37 g. Formulation GRF2 with 6% w/w binder concentration had the highest crushing strength of 8 kgF, GRF1 with 6% w/w binder concentration had the lowest friability of 0.15% while GRF3 with 3% w/w binder concentration had the shortest disintegration time of 9.25 min. There was no significant difference between the percent drug release from GRF3 tablets containing 3% w/w binder concentration and those containing 6% w/w concentration (cumulative drug release being 83% and 80% in 60 minutes). Conclusion: Nanocrystallization of griseofulvin modulated with the inclusion of Polysorbate 80 enhances the delivery of the drug but higher binder concentration is required to ensure good tablet strength.